Distribution of Inheritance Among Different Religions: A Perspective from Islamic Sociology of Law Atho’ Mudzhar - Abdur Rohman Wahid (Al-Syakhsiyyah: Journal of Law and Family Studies, 2025)
The distribution of inheritance among heirs of different religions often creates tension between the formal legal provisions in the Compilation of Islamic Law (KHI), which does not recognize cross-religious inheritance rights, and the social practices of society, which tend to resolve such issues through family deliberation. This gap highlights the need for an approach that can bridge normative law and the pluralistic social reality in Indonesia. This study employs Atho’ Mudzhar's Islamic legal sociology approach with an empirical case study method in Aditoya Hamlet, Jatigreges Village. Data was collected through observation, interviews, and document analysis, then validated through triangulation. The findings reveal that the local community prioritizes family values and social harmony over KHI provisions, leading to inheritance distribution through deliberation. This approach aligns with the principles of maqāṣid al-sharī’ah and contextual ijtihād oriented toward justice and public benefit. The study recommends a reformulation of the KHI to be more responsive to the realities of a multicultural society without neglecting the foundational principles of sharia. Through a sociological perspective, Islamic inheritance law can become more adaptive and inclusive.